Player movement patterns in an elite junior Australian Rules Football Team: An exploratory study - Veale, J. P.; Pearce, A. J.; Carlson, J. S. (Journal of Sports Science & Medicine, 2007)
This study explored the physical movement patterns associated with an elite Under 18 Australian Football (AF) team. Five field positions were selected with observations recording the number and relative per cent of "working" efforts (jogging, running, and sprinting), "resting" efforts (walking) and the total distances associated with "working" or "resting" efforts. Intra-observer reliability, using test- retest method, showed correlations were r = 0.98 or greater. The Wing position covered 11,877 m, the greatest total distance during an entire game, whilst the HBF and Centre positions both recorded 11,545 m and 11,537 m respectively and the Ruck position covered 9,203 m. The HBF recorded the greatest frequency of 'working' and 'resting' efforts (180 and 182 respectively), whilst the Wing (166 and 158), Centre (162 and 149) and Ruck (161 and 166) showed similarities in their results. The Wing position recorded the longest average distance per 'working' effort (58 m) whilst the Centre position recorded the longest average distance per 'resting' effort (17 m). Results also show the completion of less total efforts and smaller total distances, in Under 18 players, recorded compared to professional senior AF data. The results from this study suggest that further in-depth research is required into movement patterns and game activity demands in this AF playing group.